Multidisciplinary Oral Rehabilitation of a Severely Compromised Dentition - Carlo Maiorana; Dario Andreoni; Paola Polacco; Pier Paolo Poli (Case Reports in Dentistry)
The decision-making process of complex clinical cases should involve multiple specialists to obtain a predictable result on a long-term basis. In view of the above, the present report is aimed at describing the multidisciplinary management of a partially edentulous female patient presenting with a severely compromised residual dentition. To improve function and aesthetics, the treatment combined multiple extractions, temporary rehabilitation with a complete removable denture, guided bone regeneration and implant insertion, soft tissue management, tooth alignment, and restorative dentistry. Thus, several dental branches were embraced during the treatment phases, including oral surgery and implantology, periodontology, orthodontics, and prosthodontics. The involvement of different specialists ensured the achievement of a good result from biological, functional, and aesthetic aspects. The patient was satisfied with the final outcome. In conclusion, to meet the patient’s expectations particularly in complex clinical situations, the interdisciplinary approach becomes essential from the early phases in order to identify the ideal treatment plan with the correct time sequence.